Combat Experience and Problem Drinking in Veterans: Exploring the roles of PTSD, coping motives, and perceived stigma - Miller, Stephen M. (Addict Behav, 2016)
PURPOSE: The current investigation sought to illustrate the etiology of adverse alcohol consequences in young adult veterans using a path analytic framework. METHODS: A total of 312 veterans aged 19–34 were enrolled in a larger intervention study on alcohol use. At baseline, participants completed measures of combat severity, PTSD symptom severity, and drinking motives to cope. At one month follow-up, participants completed measures of perceived stigma of behavioral health treatment seeking and past 30-day alcohol consequences. RESULTS: After entering the covariates of age, gender, race/ethnicity, and past year behavioral health treatment utilization, a path analytic model demonstrated a good fit to the data predicting alcohol consequences in this population. Further, a separate exploratory analysis confirmed that both drinking motives to cope and perceived stigma of behavioral health treatment seeking mediated the link between PTSD symptom severity and alcohol consequences. CONCLUSIONS: The current model expands upon prior research showing the relationship between combat severity and alcohol use behavior in young adult veterans. Results support the notion that veterans with PTSD symptoms may drink to cope and that perceived stigma surrounding help seeking may further contribute to alcohol related problems.